(untitled) (European Journal of Formal Sciences and Engineering, 2024)
Rockfall dynamics is a complex function of the location of the detachment point and the geometry and mechanical properties of both the block and the slope. Theoretically, knowing the initial conditions, the slope geometry, and the relationships describing the energy loss at impact or by rolling, it should be possible to compute the position and velocity of a block at any time. Nevertheless, relevant parameters are difficult to ascertain both in space and time, even for an observed event. Usually, the geometrical and geomechanically properties of the blocks (size, shape, strength, fracturing) and the slope (gradient, length and roughness, longitudinal and transversal concavities and convexities, grain size distribution, elastic moduli, water content, etc.), and the exact location of the source areas are unknown. In this paper, the sources of potential rock fallings involve a rocky area including between km 13+550 and km 13+600 in the new road of Vlora city in Albania. The area is characterized by a rock ridge, shaped like a dome, located few tens of meters above the design road. The purpose of this paper is the rock slope analysis. This analysis consists mainly of defining the sources of falling rocks, estimating the causes (by toppling, rock slides, single blocks) the size, the geometry, and type of blocks, the structural arrangement of joints, etc.